Using host and bacterial genetic approaches to define virulence strategies and protective immunity during Mycobacterium tuberculosis infection - Andrew J. Olive (mSphere)
ABSTRACT Infections with Mycobacterium tuberculosis (Mtb) resulted in over one million deaths in 2024, the highest number for any infectious disease. With no vaccines that protect against pulmonary tuberculosis (TB) and the challenges associated with antibiotic therapy, there is a critical need to better understand host-Mtb interactions to help curb this major public health problem. Mtb is arguably the most successful human pathogen, and it survives in diverse environments, resulting in heterogeneous disease outcomes in patients. Five years ago, in my commentary in mSphere, I discussed how Mtb virulence strategies that sense, adapt, and evade killing in the host can be uncovered using genetic approaches. Here, I will come full circle to highlight genetic approaches that recently uncovered new mechanisms regulating protective host responses and Mtb survival tactics. The goal is to highlight a genetic framework to probe a range of unexplored Mtb phenotypes, increase our understanding of host-Mtb interactions, and identify new therapeutic targets that may help prevent TB.